Clinical study of squamous cell carcinoma of the buccal mucosa: A review of 17 cases - SHINGAKI, SUSUMU; NAKAJIMA, Tamio; KOBAYASHI, Yutaka (Japanese Journal of Oral and Maxillofacial Surgery, 1997)
Seventeen patients with squamous cell carcinoma of the buccal mucosa were studied. The subjects included 11 men and 6 women. 44 to 80 years of age (mean, 67.6 years). There were 3 stage I patients (17.6%), 5 stage II patients (29.4%), 2 stage II patients (11.8%), and 7 stage IV patients (41.2%). Initial treatment consisted mainly of surgery in 8 cases (47.1%), radiotherapy in 5 cases (29.4%), and a combination of surgery and radiotherapy in 4 cases (23.5%). Regional lymph node metastases were observed in 4 cases (23.5%) on initial examination and in 1 case later. Radical neck dissections were performed in all cases. The disease was uncontrollable in 2 cases. Local recurrence occurred in 5 cases (29.4%). The rate of recurrence in T 3 +T 4 cases was significantly higher than that in T 1 +T 2 cases (t-test: p<0.05). The five-year cumulative survival rate calculated by the Kaplan-Meier method, was 52.3% for the entire group of 17 patients. Outcome was not good in patients with advanced lesions (T3, T4) and tumors showing diffuse invasion. Local recurrence occurred